The Regulatory Effect of Coaggregation Between Fusobacterium nucleatum and Streptococcus gordonii on the Synergistic Virulence to Human Gingival Epithelial Cells - Yang, Ruiqi; Liu, Tingjun; Pang, Chunfeng; Cai, Yanling; Lin, Zhengmei; Guo, Lihong; Wei, Xi (Frontiers in Cellular and Infection Microbiology, 2022)
In subgingival plaque biofilms, Fusobacterium nucleatum is closely related to the occurrence and development of periodontitis. Streptococcus gordonii, as an accessory pathogen, can coaggregate with periodontal pathogens, facilitating the subgingival colonization of periodontal pathogens. Studies have shown that F. nucleatum can coaggregate with S. gordonii and colonize the subgingival plaque. However, most studies have focused on monocultures or coinfection of species and the potential impact of coaggregation between the two species on periodontal interactions to human gingival epithelial cells (hGECs) remains poorly understood. The present study explored the effect of coaggregation between F. nucleatum and S. gordonii on subgingival synergistic virulence to hGECs. The results showed that coaggregation inhibited the adhesion and invasion of F. nucleatum to hGECs compared with that in the F. nucleatum monoculture and coinfection group. Coaggregation and coinfection with F. nucleatum both enhanced S. gordonii adhesion to hGECs, but neither of the two groups affected S. gordonii invasion to hGECs compared with S. gordonii monoculture. The gene expression levels of TLR2 and TLR4 in hGECs in the coaggregation group were higher than those in the monoculture groups but lower than those in the coinfection group. Compared with coinfection, the coaggregation inhibited apoptosis of hGECs and promoted the secretion of the proinflammatory cytokines TNF-α and IL-6 by hGECs, showed a synergistic inflammatory effect, while coaggregation inhibited the secretion of the anti-inflammatory cytokine TGF-β1. Coaggregation enhanced the phosphorylation of p65, p38, and JNK proteins and therefore activated the NF-κB and MAPK signaling pathways. Pretreatment with a pathway antagonist/inhibitor decreased the phosphorylation levels of proteins and the secretion of TNF-α and IL-6. In conclusion, coaggregation inhibited the adhesion and invasion of F. nucleatum to hGECs. However, it enhanced the adhesion of S. gordonii to hGECs. Compared with coinfection, coaggregation inhibited the apoptosis of hGECs. The coaggregation coordinately promoted the secretion of TNF-α and IL-6 by hGECs through the TLR/NF-κB and TLR/MAPK signaling pathways while inhibiting the secretion of TGF-β1, thus aggravating the inflammatory response of hGECs.